PSYCHOLOGICAL ASPECTS OF NEGOTIATION - ZRYBNIEVA, IRYNA (My University, 2021)
Effective negotiation tactics must be based on communication skills, psychological influence, and business ethics, since the result of decision-making largely depends on negotiation skills. Knowledge of the psychology of negotiation and skillful use of psychological methods and techniques in the negotiation process is especially important for resolving disagreements, avoiding disputes, conflicts, concluding successful deals, establishing strong partnerships, maximizing mutual benefits.
Keywords: Negotiation; Business negotiations; communication skills; psychological influence